Benjamin Franklin - D$1 (BAulaire, Ingri,s 1904-; D$1 (BAulaire, Edgar Parin,s 1898- (Garden City, N.Y., Doubleday, 1950)
A biography of the witty author, scientist, and statesman who helped with the Declaration of Independence and the Constitution and became the first ambassador of the United States of America.
Keywords: Franklin, Benjamin, -- 1706-1790 -- Juvenile literature; Franklin, Benjamin, -- 1706-1790.; Statesmen